2012
DOI: 10.1111/j.1742-4658.2012.08573.x
|View full text |Cite
|
Sign up to set email alerts
|

Balance of human choline kinase isoforms is critical for cell cycle regulation

Abstract: The enzyme choline kinase (CK), which catalyzes the phosphorylation of choline to phosphorylcholine in the presence of ATP, has an essential role in the biosynthesis of phosphatidylcholine, the major constituent of all mammalian cell membranes. CK is encoded by two separate genes expressing the three isoforms CKα1, CKα2 and CKβ that are active as homodimeric or heterodimeric species. Metabolic changes observed in various cancer cell lines and tumors have been associated with differential and marked up‐regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 68 publications
2
32
0
Order By: Relevance
“…The protein is overexpressed in several cancers through amplification or mRNA upregulation. In cancer cells, overexpression of CHKA is associated with transformation of normal cells to cancer [18], and conversely, depletion of CHKA by RNAi can reduce cell survival and tumor growth (Supplementary Figure S1C and[8, 20, 36]). To date, attention in the field of cancer has focused on the requirement of choline together with channeling of fatty acids into PC synthesis to support the increased need for membrane synthesis; however, this mechanism alone does not explain the effects of chemical inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein is overexpressed in several cancers through amplification or mRNA upregulation. In cancer cells, overexpression of CHKA is associated with transformation of normal cells to cancer [18], and conversely, depletion of CHKA by RNAi can reduce cell survival and tumor growth (Supplementary Figure S1C and[8, 20, 36]). To date, attention in the field of cancer has focused on the requirement of choline together with channeling of fatty acids into PC synthesis to support the increased need for membrane synthesis; however, this mechanism alone does not explain the effects of chemical inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…CHK exists in at least three isoforms: CHKA1, CHKA2 and CHKB encoded by two separate genes, of which the A, but not the B isoforms, have been implicated in cancer [6]. While under normal physiological conditions, CCT is the rate-limiting step of the pathway, CHKA is anticipated to be a major regulator in cancer [7, 8]. …”
Section: Introductionmentioning
confidence: 99%
“…Among the multiple enzymes involved in the biosynthesis of phosphatidylcholine, the major structural component of eukaryotic cell membranes, choline kinase is the first enzyme of the Kennedy pathway responsible for catalyzing the phosphorylation of free choline to form phosphocholine [5, 6]. In mammalian cells, choline kinase is encoded by two separate genes, choline kinase alpha (CHKA) and beta (CHKB), of which only CHKA has a central role in sustaining the biosynthesis of phosphatidylcholine [7, 8]. To date, Increased expression and enzymatic activity of CHKA has been identified in a variety of human malignancies including breast, lung, colorectal, bladder, prostate, ovarian, endometrial carcinomas, osteosarcoma, and T-cell lymphoma [918].…”
Section: Introductionmentioning
confidence: 99%
“…[3] A recent manuscript has clearly shown that a potent anticancer effect inducing maximum apoptosis is only achieved when CHOKa expression is specifically diminished without CHOKb levels being affected. [4] Compounds that are selective and potent against CHOKa are therefore proposed as valuable tools for treatment of cancer. We have previously described a new series of unsymmetrical monocationic compounds that showed moderate potency against CHOK in HepG2 cells.…”
mentioning
confidence: 99%